2017
DOI: 10.1515/opag-2017-0065
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Nutrient Use Efficiency of Bread Wheat (Triticum Aestivum L.) as Influenced by Time and Rate of Nitrogen Application in Enderta, Tigray, Northern Ethiopia

Abstract: Open Agriculture. 2017; 2: 611-624 efficiency of 75% was obtained in response to the rate of 69 kg N ha -1 applied in three splits of 1/4 at planting, ½ at tillering, and 1/4 at anthesis. The equivalent values for the highest apparent recovery was 81% in the 2014 cropping season. The highest agronomic efficiency of 25 kg kg -1 and utilization efficiency of 55 kg kg -1 were recorded at the rate of 46 kg N ha -1 in three splits of 1/4 at planting, ½ at tillering and ¼ at anthesis. The equivalent values in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
7
10
0
Order By: Relevance
“…Similarly, PE K ranged from 39.0 to 63.3 kg kg -1 observed in wheat is comparable to PE K range of 45.0 to 48.9 kg kg -1 recorded by [ 66 ] and PE K range of 49 to 96 kg kg -1 obtained by [ 61 ] and lower than the maximum PE K of 83.1 kg kg -1 recorded by [ 69 ]. Similar to our findings, the highest PE was recorded with the application of lower level of K [ 74 , 75 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, PE K ranged from 39.0 to 63.3 kg kg -1 observed in wheat is comparable to PE K range of 45.0 to 48.9 kg kg -1 recorded by [ 66 ] and PE K range of 49 to 96 kg kg -1 obtained by [ 61 ] and lower than the maximum PE K of 83.1 kg kg -1 recorded by [ 69 ]. Similar to our findings, the highest PE was recorded with the application of lower level of K [ 74 , 75 ].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, Agronomic Efficiency (AE) and Partial Factor Productivity (PFP) are more relevant in this type of study. Similar kind of positive correlation between AE and crop yield was also reported by Zemichael et al (2017)…”
Section: Correlation Between Nutrient Use Efficiency and Grain Yieldsupporting
confidence: 86%
“…A declining pattern in AE was observed with raising N from 30 to 120 kg ha –1 ( Arduini et al, 2006 ) and 120 to 360 kg ha –1 ( Belete et al, 2018 ). Zemichael et al (2017) also reported decreasing trend in NUE traits with increasing doses of nutrients, explaining better performance with idea of supplying N at maximum absorption period resulting in higher biomass production while, supplying N at higher doses at planting time results in reduced uptake of N and S loses of nutrient with reduced efficiency.…”
Section: Discussionmentioning
confidence: 84%